Keterampilan Guru Abad 21 Dalam Mengurangi Learning Loss Pada Peserta Didik (Kajian Fenomenalogis Di SMA Kabupaten Sumbawa) - Haris, Andi; Sentaya, I Made; Sulindra, I Gusti Made (Jurnal Ilmiah Mandala Education (JIME), 2022)
The importance of 21st century teacher skills that must be possessed to minimize learning loss in certain situations (learning loss) becomes a foothold that must be studied, reviewed by all practitioners, lecturers, teachers, and educational institutions. This learning loss phenomenon has become a serious problem for students in the midst of Covid-19 and coupled with the limited internet access in the mountainous region of the southern part of Sumbawa. In addition, the skills of 21st century teachers are the main capital in utilizing information and communication technology. Based on qualitative research with a phenomenological approach that uses Interpretative Phenomenological Analysis (IPA) analysis shows that (1) 21st century communication skills possessed by educators and students show that understanding the role of multimedia in accessing, managing materials, videos, assignments, attendance, and simulating using various platforms (google meet, google classroom, whatsapps, and email) in blended learning is quite good, (2) the ability to create information in various forms and media; create communication (oral, written and in the form of multimedia); and transfer learning from one domain to another; sharing and communicating digital information is a major detail of information and media literacy skills; communication skills; and self-direction skills possessed by 21st century educators.